Evaluating system dependability in a co-design framework - Lajolo, M.; Rebaudengo, M.; Reorda, M.S.; Violante, M.; Lavagno, L. (Design, Automation, and Test in Europe Conference and Exhibition 2000 : proceedings, Paris, France, March 27-30, 2000, 2000)
The widespread adoption of embedded microprocessor-based systems for safety critical applications mandates the use of co-design tools able to evaluate system dependability at every step of the design cycle. In this paper, we describe how fault injection techniques have been integrated in an existing co-design tool and which advantages come from the availability of such an enhanced tool. The effectiveness of the proposed tool is assessed on a simple case study.